2022
DOI: 10.3389/fendo.2022.1069625
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin in relation to gestational diabetes and metabolic risk in pregnancy and postpartum: A systematic review and meta-analysis

Abstract: ContextPre-clinical evidence suggests that prolactin has important metabolic functions in pregnancy and postpartum, in addition to lactogenic actions.ObjectiveTo explore the relationship between prolactin and maternal metabolic outcomes in human pregnancy and postpartum, particularly in relation to gestational diabetes mellitus (GDM).Data sourcesMEDLINE via OVID, CINAHL plus, Embase.Study selectionEligible studies included women who were pregnant or up to 12 months postpartum, reporting at least one maternal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…A recent meta-analysis confirmed that elevated prolactin was associated with lower beta-cell function and higher insulin sensitivity in the postpartum period. However, the direction of causality remains unclear ( 29 ). Lipolysis is also known to contribute to decreasing β-cell function ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis confirmed that elevated prolactin was associated with lower beta-cell function and higher insulin sensitivity in the postpartum period. However, the direction of causality remains unclear ( 29 ). Lipolysis is also known to contribute to decreasing β-cell function ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This unstable metabolic state increases blood glucose and free fatty acid levels, further contributing to GDM development. However, no consensus exists on whether these hormones contribute to GDM, as some systematic reviews have discovered no association between placental prolactin and prolactin and an increased GDM risk ( 43 , 61 ). Therefore, further large-scale studies are needed.…”
Section: Placental Adipokines and Cytokinesmentioning
confidence: 99%
“…Results for hPL have been synthesised and reported elsewhere [14]. Eleven of the PRL studies explicitly examined PRL in relation to pre-existing maternal metabolic conditions and were included in the present review; the remaining 24 examined PRL in relation to broader aspects of maternal metabolism (including gestational diabetes mellitus) and have been reported elsewhere [15].…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%